2016
DOI: 10.1186/s13104-016-2078-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical teams’ attitudes and opinions towards the safety of surgical procedures in public hospitals in the Brazilian Federal District

Abstract: BackgroundAccording to the World Health Organization, the WHO surgical safety checklist can prevent complications, improve communication and contribute to postsurgical safety culture; hence, there is a need to investigate the attitudes and opinions of surgical teams regarding safety utilizing the WHO instrument. The aim of this study was to assess the attitudes and opinions towards surgical safety among operating room professionals in three public hospitals in the Brazilian Federal District.MethodsA cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 32 publications
2
23
0
8
Order By: Relevance
“…In the Brazilian context, some initiatives to measure and evaluate safety culture in institutions have been registered 8 - 11 , revealing weaknesses in different aspects. There still prevails the perception that failures in patient safety point to individual responsibilities and, consequently, punitive actions for the professional.…”
Section: Introductionmentioning
confidence: 99%
“…In the Brazilian context, some initiatives to measure and evaluate safety culture in institutions have been registered 8 - 11 , revealing weaknesses in different aspects. There still prevails the perception that failures in patient safety point to individual responsibilities and, consequently, punitive actions for the professional.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous reports that have demonstrated that the use of checklists enhanced communications across professional lines. [ 11 12 13 14 15 ] Russ et al . in a systematic review of safety checklists came to a conclusion that they are beneficial for operating room teamwork and communication and may be a way through which patient outcomes can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, apesar de iniciativas para a implementação da LVSC nos hospitais, constata-se escassez de publicações sobre a problemática (MOTA FILHO et al, 2013;PANCIERI et al, 2013;FREITAS et al, 2014;DIEGO et al, 2016;SANTANA;RODRIGUES;EVANGELISTA, 2016), principalmente sobre o processo de implementação dessa ferramenta nos serviços de saúde .…”
Section: Lista De Quadrosunclassified
“…As pesquisas conduzidas no contexto nacional tiveram enfoques diferentes, tais como: taxa de adesão ao uso da LVSC e impacto na morbimortalidade dos pacientes ; adesão da equipe ao uso da lista (FREITAS et al, 2014); opinião e atitudes da equipe sobre a lista (PANCIERI et al, 2013;SANTANA;RODRIGUES;EVANGELISTA, 2016;DIEGO et al, 2016); e conhecimento de cirurgiões sobre a ferramenta (MOTA FILHO et al, 2013).…”
Section: Lista De Quadrosunclassified
See 1 more Smart Citation